Legal Protection Of Creditors Over Collateral In Bankruptcy - Komang Krisna Yustika Putra; I Ketut Kasta Arya Wijaya; I Wayan Kartika Jaya Utama (Jurnal Smart Hukum (JSH), 2026)
Legal protection of creditors over collateral in bankruptcy requires a systematic interpretation of mortgage law, bankruptcy law, and banking asset-quality regulation. This article analyzes the legal position of separatist creditors holding mortgage rights and the protection of banks in resolving foreclosed collateral assets when debtors are declared bankrupt. The study uses normative legal research with statutory, conceptual, and case approaches, focusing on the interaction between Law Number 4 of 1996 concerning Mortgage Rights and Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. The analysis shows that mortgage holders retain preferential and executorial rights, but those rights are procedurally restricted by bankruptcy law through a 90-day stay period and a two-month execution period after insolvency. Foreclosed collateral may be protected only when the takeover is valid, voluntary, properly documented, fairly valued, and not contrary to the collective nature of bankruptcy. The study argues that the principle of lex specialis derogat legi generali makes bankruptcy law prevail in bankruptcy proceedings, while preventive and repressive protection must be strengthened through harmonized regulation, authentic documentation, curator oversight, and clearer temporal standards for collateral execution